Perancangan Sistem Informasi Retensi Rekam Medis Berbasis Web di Rumah Sakit Limijati - Rian Adhiansyah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Abstract In this study, we want to know the retention system that runs at RSIA Limijati and can overcome existing obstacles. This refers to the problem at RSIA Limijati, namely the disruption to the filing or storage of medical record files because the medical record files are full and sufficient resources are hampered for the retention process. With this problem, a Medical Record File Retention Information System solution was made to overcome the existing problems. This research method uses qualitative methods to describe existing phenomena. The data collection method uses interviews and field observations. The software development method uses Waterfall, the design uses Data Flow Diagrams (DFD), Entity Relationship diagrams (ERD) and is implemented with the PHP programming language, the database uses Mysql so that the data storage system is safe. The results of integration and system testing using the Black-Box-Test method show that the retention application functions well with a 100% success rate. The results of this study are proven to facilitate the retention process in the medical record section, do not spend a lot of time and do not interfere with other work. In order for the system to run smoothly and safely, it must be maintained and checked regularly.